2020
DOI: 10.1038/s41598-020-78442-8
|View full text |Cite
|
Sign up to set email alerts
|

The impact of aspirin on Klebsiella pneumoniae liver abscess in diabetic patients

Abstract: In this study, we aimed to investigate the impact of aspirin on the risk of pyogenic liver abscess caused by Klebsiella pneumoniae (KP-PLA) and invasive KP-PLA syndrome (IKPS) in diabetic patients. Diabetic patients who were propensity-score matched were retrospectively included from hospital-based database. Kaplan–Meier approach with a log-rank test was used to compare the cumulative incidences of KP-PLA including IKPS between aspirin users and non-users. Totally, 63,500 patients were analyzed after propensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…Liu et al identified 5912 patients with PLA and evaluated recurrence PLA rates between ASA users and non-users, which were 42.5 and 74.6 per 1000 person-years of follow-up, respectively [ 77 ]. Similar findings were reported in a large cohort of diabetic patients, with ASA continuous intake for >90 days associated with a lower risk of PLA [ 78 ].…”
Section: Resultssupporting
confidence: 89%
“…Liu et al identified 5912 patients with PLA and evaluated recurrence PLA rates between ASA users and non-users, which were 42.5 and 74.6 per 1000 person-years of follow-up, respectively [ 77 ]. Similar findings were reported in a large cohort of diabetic patients, with ASA continuous intake for >90 days associated with a lower risk of PLA [ 78 ].…”
Section: Resultssupporting
confidence: 89%
“…However, rarely, it can also cause infections in other organ systems such as in the gastrointestinal tract, meninges, eyes, and ears. Most commonly, K. pneumoniae causes infection in alcoholic patients and those with diabetes, especially if uncontrolled, which was recently reported in at least three case reports linking diabetes and hepatic abscesses [ 1 , 8 , 9 ], and at least one case report linking diabetes and biliary abscesses [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the population size is smaller than that of the NHI database, the CGRD contains more clinical information (laboratory results, examination and pathological reports, medical and nursing records) than the NHI database. To date, CGRD has been widely used to establish real-world evidence studies in many fields [ [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] ]. However, previous studies pointed out that selection bias and loss of follow-up were two major limitations of CGRD [ 2 , 4 , 5 , 8 , 16 ].…”
mentioning
confidence: 99%